PERAN GURU DALAM PENDIDIKAN DAN PENGUATAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB SISWA DI SDK SANTO YUSUF MADIUN - Timang, Mawar Agustina Feronika; Widiatna, Alexius Dwi (CREDENDUM: Jurnal Pendidikan Agama, 2025)
This study aims to describe the role of teachers in fostering character education of the students at Saint Yusuf Catholic Elementary School, Madiun city. The research focused on the role of teachers as role models and mentors, their understanding of the values of discipline and responsibility, and the strategies used to foster the character of discipline and responsibility of the students. This study employs a qualitative approach with data collected through observation, in-depth interviews, and documentation.The findings indicated that teachers actively participate in activities such as morning assemblies, communal prayers, recollections, religious events, and the reinforcement of positive habits. In these activities, teachers serve as examples and guide students to act with discipline and responsibility. Character education aims to develop students who are not only academically competent but also have strong character, faith, discipline, and a sense of responsibility.